An interior-point trust-region polynomial algorithm for convex quadratic minimization subject to general convex constraints - Lu, Ye; Yuan, Ya-Xiang (Optimization methods & software, 2008)
An interior-point trust-region algorithm is proposed for minimization of a convex quadratic objective function over a general convex set. The algorithm uses a trust-region model to ensure descent on a suitable merit function. The complexity of our algorithm is proved to be as good as the interior-point polynomial algorithm.